Screening of Inhibitors against Glycolipid Transfer Protein - Andersson, Amanda (My University, 2025)
The human glycolipid transfer protein (GLTP) is a membrane-associated lipid transfer protein regulating the transport of glycosphingolipids and plays a vital role in cellular lipid homeostasis. Due to GLTP’s potential involvement in diseases such as cancer, neurodegeneration, and viral infections, it has emerged as a novel therapeutic target. However, relatively little is known about how GLTP functions within broader biological pathways, and no small-molecule inhibitors of GLTP have been identified to date. The aim of this study was to identify small-molecule inhibitors of GLTP using a structure-based virtual screening approach. The high-resolution crystal structure of wild-type GLTP in complex with a sulfatide (3-O-sulfo-galactosylceramide) was selected as the target for in silico modeling, with the sulfatide simultaneously serving as the reference ligand. Molecules from literature and two preprocessed virtual libraries, containing over 150,000 compounds in total, were docked into the GLTP lipid-binding site using the Glide (Grid-based Ligand Docking with Energetics) docking tool in Maestro. The top-scoring ligands were then evaluated using molecular mechanics-generalized Born surface area (MM-GBSA) calculations to estimate binding free energies. The most promising candidates were subsequently subjected to molecular dynamics (MD) simulations to assess the stability of the ligand–protein complexes in a computational system mimicking real physiological conditions. Several compounds from the screened databases were observed to exhibit strong and stable binding through the 500-ns MD simulation. Notably, the top inhibitor candidates interacted with the same key amino acid residues as the reference compound. These findings suggest that the identified small molecules may function as potential GLTP inhibitors with therapeutic relevance. However, as structure-based virtual screening is an in silico approach, further experimental validation through biological in vitro testing is required to confirm their inhibitory activity and therapeutic potential.
Keywords: glycolipid transport, inhibitor discovery, in silico, MM-GBSA, molecular docking, molecular dynamics, virtual screening